Spatio-temporal indexing method for biodiversity application - Abd. Kahar, Nazratul Ain (Penerbit UTM, 2007)
In order to effectively manage environmental data such as satellite photos and images, map images, and cartographic materials, a large number of environmental digital libraries have been designed and implemented such as the Ocean Biogeographic Information System (OBIS) for managing aquatic biodiversity and Global Biodiversity Information Facility (GBIF) which focuses on both flora and fauna biodiversity. The emerging of these applications need support for storing, distributing, searching, retrieving and utilizing the information so that the information can be used to its maximum potential benefit and effectiveness. There are challenges of managing these environmental data because of its variability that may end up as a very large scale of complex data which is obviously difficult to handle. However, biodiversity data cannot be simply stored in a database without considering the characteristics of biodiversity informatics and also its data type and the database to be used to store the data. This will lead to the understanding the nature of spatio-temporal data of which has the same characteristic of biodiversity data